2023
DOI: 10.1039/d2cp04497h
|View full text |Cite
|
Sign up to set email alerts
|

Hydration-induced protomer switching in p-aminobenzoic acid studied by cold double ion trap infrared spectroscopy

Abstract: Para-aminobenzoic acid (PABA) is a benchmark molecule to study solvent-induced proton site switching. Protonation of the carboxy and amino groups of PABA generates O- and N-protomers of PABAH+, respectively. Ion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Metastable isomers are often present when floppy molecules (e.g., peptides) and clusters (e.g., microhydrated ions) are cooled quickly, whether through supersonic expansion or by collisions with buffer gas in a cryogenic radiofrequency ion trap. In the latter case, this occurs when the ambient (300 K) ions undergo rapid isomer interconversion in the source region, and this dynamic ensemble is cooled by collisions with He buffer gas in the cryogenic trap.…”
Section: Introductionmentioning
confidence: 99%
“…Metastable isomers are often present when floppy molecules (e.g., peptides) and clusters (e.g., microhydrated ions) are cooled quickly, whether through supersonic expansion or by collisions with buffer gas in a cryogenic radiofrequency ion trap. In the latter case, this occurs when the ambient (300 K) ions undergo rapid isomer interconversion in the source region, and this dynamic ensemble is cooled by collisions with He buffer gas in the cryogenic trap.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 While the formation of O-protomers in ESI with protic solvents (e.g., H 2 O and CH 3 OH) is attributed to a solvent-assisted intramolecular proton transfer from the NH 3 + group to the oxygen atom (Grotthuss mechanism), [23][24][25][26] there is no experimental evidence for the formation of these solvent bridges in the gas phase. 27,28 Other than the influence of solvent, the substitution pattern of the NH 2 and COOR groups on the ring (ortho, meta, and para) also influences the protonation of the oxygen atom of ABA derivatives. An IM-IR study showed that p-ABA forms both N-and O-protomers, while m-ABA and o-ABA exhibit only N-protonation.…”
Section: Introductionmentioning
confidence: 99%
“…, H 2 O and CH 3 OH) is attributed to a solvent-assisted intramolecular proton transfer from the NH 3 + group to the oxygen atom (Grotthuss mechanism), 23–26 there is no experimental evidence for the formation of these solvent bridges in the gas phase. 27,28…”
Section: Introductionmentioning
confidence: 99%
“…In solution-phase experiments, the noncovalent interactions between a solute and a solvent are difficult to characterize due to the spectral interference from solvent molecules that do not participate in the solvation. Solvated clusters are regarded as a model for clarifying the nature of solvation. One can interrogate the microsolvation effect using this double ion trap technique because the degree of solvation (i.e., number of solvent molecules) can be precisely selected by mass spectrometry. , In this study, the hydration effect on the conformation of Na + VM was examined by cryogenic double ion trap IR spectroscopy. We have found a significant hydration effect on the Na + VM conformations (not observed for K + VM), as a function of hydration number.…”
mentioning
confidence: 99%